Reassessing Thamaniyyah in Islamic Monetary Jurisprudence: Implications of Paper Currency for Zakat and Waqf Management - Nahid Ayad; Safa Alrumayh; Abdulrauf Atia; Entisar Alatrish; Karima Elhaj; Laylay Hasan; Zaynab Omar; Mowafg Masuwd; Abtisam Rayhan (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
The transformation of monetary systems from gold and silver to fiat and digital currencies has generated significant challenges for contemporary Islamic jurisprudence. Central to these debates is the concept of thamaniyyah (moneyness), which determines the legal status of money and the application of rulings related to riba, Sarf, zakat, debts, and financial obligations. Scholars continue to disagree on whether thamaniyyah is a legally effective cause (ʿillah sharʿiyyah) or a customary attribute (wasf ʿurfi) arising from social acceptance and economic practice. Using a qualitative doctrinal methodology that combines analytical, comparative, and maqasid-oriented approaches, this study examines classical juristic writings, works of usul al-fiqh, contemporary Islamic finance literature, and fiqh academy resolutions. The findings show that classical scholarship supports both interpretations: some jurists treated thamaniyyah as an operative cause for extending monetary rulings, while others emphasized custom, public acceptance, and institutional recognition. The study argues that thamaniyyah is best understood as a custom-based legal attribute that originates in social and economic recognition but acquires binding legal consequences within the Shariʿah framework. This interpretation preserves doctrinal continuity while enabling Islamic law to address fiat money, inflation, digital currencies, and future monetary transformations.